Sexual Refusal by Indonesian Female University Students - Yusuf, Marwah Juwita (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
This research aims to find out the most frequent strategies used by Indonesian female university students in expressing their refusal to sexual intercourse and the refusal strategies that they used to refuse the sexual intercourse. This research was carried out in 14 cities in Indonesia with 638 respondents (307 female respondents and 331 male respondents). The data were collected by using Discourse Completion Task (DCT) and interview to identify the sexual refusal strategies by female university students. The data were analyzed by using reconstructed conversation and Speech Act theory by Searle (1976) and Politeness of Brown & Levinson (1989) as a supporting theory. This research finds seven frequent strategies used by Indonesian female university students to refuse the sexual intercourse. The first is pregnancy risk reason (37,07%), next is legality reason (21,59%), postponement (15,48%) is at the third place, direct refusal non-performative (14,05 %) as the forth and is followed by religiouos reason (7,94%) at the fifth, direct refusal performative (2,24%) is the sixth and the last strategy is topic switch (1,63%). The data also show that most of Indonesian female university students refuse the sexual intercourse by giving pregnancy risk reason such as fear of being pregnant. From the reconstructed conversation, the data analysis show that most of them use Indirect Speech Act to maintain the relationship, the politeness and the positive face want of their boyfriend.